Impacts of sweeping agricultural marketing reforms in a poor state of India: Evidence from repeal of the APMC act - Kishore, Avinash; Kishore, Prabhat; Roy, Devesh; Saroj, Sunil (International Association of Agricultural Economists, 2021)
Bihar, among the poorest and least industrialized states in India implemented the most far reaching agricultural market reforms in 2006 by removing law (APMC act) that restricted farmers to selling in government regulated markets. With the unmatched radicalness of this reform, its impacts, and implications for farmers, has not been analyzed. Taking the natural experiment of repeal of APMC, we first assess the impacts on market level outcomes employing synthetic control method and find that repeal of APMC act did not lead to increase in market efficiency, reduction in the wholesale-retail price wedge and wholesale prices of food items. Yet, at the farmer level, by uniquely employing panel data on farm harvest prices (FHP) and farming characteristics, we find evidence of impacts on FHP that varies by crop. The DID estimates show that repeal of APMC actually impacted in terms of lower FHP of paddy with a larger negative effect on marginal farmers. FHP of maize, grown mainly for exports to other states and countries and where new entry of buyers took place, was higher possibly because of increased competition among buyers and use of alternate and more direct channels of procurement from farmers that increased marketing efficiency.